Subjective assessment of sports success in wheelchair rugby - proposal of a new research tool. - Tasiemski, T.; Bauerfeind, J. (Human Movement, 2013)
Purpose: The main purpose of this study was to design and perform a preliminary psychometric analysis of a measure in the subjective assessment of sports success in wheelchair rugby (WR). An additional objective of this study was to assess potential differences in the subjective assessment of sports success between rugby players who play in the first and second Polish Wheel-chair Rugby League (PWRL). Methods: Thirty WR players who played in the first (n= 11) and second PWRL (n= 19) completed the newly-created subjective Assessment of sports success in Wheelchair Rugby (SASS-WR) scale and a questionnaire collecting demographic, career, and sports training data. Results: The SASS-WR scale was found to be a valid and reliable measure of sports success in WR. The final version consists of 12 items defining four dimensions of sports success: (1) Individual sports success of the Player, (2) National sports success of the Team, (3) International sports success of the Team, (4) social and Personal success of the Player. The players in the first league were significantly more focused on achieving individual sports success as well as having their team achieve national and international sports success when compared with the players in the second league. Social and personal success (the fourth dimension of the SASS-WR) was more important for the second league players than first league players, although this difference was not significant. Conclusions: The findings suggest that the SASS-WR scale can serve as a valuable diagnostic tool in assessing sports success among WR players.